2012
DOI: 10.1039/c2cc36199j
|View full text |Cite
|
Sign up to set email alerts
|

γ-Selective directed catalytic asymmetric hydroboration of 1,1-disubstituted alkenes

Abstract: Directed catalytic asymmetric hydroborations of 1,1-disubstituted alkenes afford γ-dioxaborato amides and esters in high enantiomeric purity (90–95% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…1,2 We have developed efficient carbonyl-directed CAHBs of unsaturated amides and esters capable of chelating to Rh(I) through a two-point binding mechanism 3 and shown that the presence of an aryl substituent on the alkene is not required to obtain high levels of enantioselectivity. 4,5 For example, rhodium-catalyzed CAHBs of the β,γ-unsaturated amides and esters illustrated in Figure 1 lead, in the case of ( E )- or ( Z )-1,2-disubstituted and -trisubstituted alkenes 1 , to enantioselective borylation at the β-carbon yielding the β-hydroxycarbonyl compounds 2 after oxidation. In the case of β,γ-methylidene derivatives 3 , CAHB affords a γ-borylated intermediate which upon oxidation affords the γ–hydroxycarbonyl derivative 4 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 We have developed efficient carbonyl-directed CAHBs of unsaturated amides and esters capable of chelating to Rh(I) through a two-point binding mechanism 3 and shown that the presence of an aryl substituent on the alkene is not required to obtain high levels of enantioselectivity. 4,5 For example, rhodium-catalyzed CAHBs of the β,γ-unsaturated amides and esters illustrated in Figure 1 lead, in the case of ( E )- or ( Z )-1,2-disubstituted and -trisubstituted alkenes 1 , to enantioselective borylation at the β-carbon yielding the β-hydroxycarbonyl compounds 2 after oxidation. In the case of β,γ-methylidene derivatives 3 , CAHB affords a γ-borylated intermediate which upon oxidation affords the γ–hydroxycarbonyl derivative 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[6g] In this case,d uring formation of the transition states,stabilization of the accumulating negative charge on the copper-bound carbon atom by the nearby polar directing group was responsible for the observed regioselectivity. [8] Herein, we report ah ighly distal-selective hydroboration of aliphatic internal alkenes using the readily available iridium dimer precursor [Cp*IrCl 2 ] 2 (Cp* = pentamethylcyclopentadienyl) [9] as the catalyst. [8] Herein, we report ah ighly distal-selective hydroboration of aliphatic internal alkenes using the readily available iridium dimer precursor [Cp*IrCl 2 ] 2 (Cp* = pentamethylcyclopentadienyl) [9] as the catalyst.…”
mentioning
confidence: 99%
“…This unusual selectivity complements those of reported Cu-, Rh-, and Ir-catalyzed hydroboration reactions.The current method tolerates avariety of b,g-a nd g,d-unsaturated carbonyl compounds,a ffording the borylated products in good to excellent regioselectivity (up to 99:1). Fortunately,inthe presence of bulkier ligands,t he reaction facilely afforded product 2a in good to excellent yield with consistently excellent regioselectivity (2a/(3a+ 4a) = 98:2;T able 1, entries [5][6][7][8][9][10]. [9c, 10] To initiate our study,w ec hose b,g-unsaturated amide 1a as our model substrate.I nitial attempts using [MCl(COD)] 2 (M = Rh, Ir) as the catalyst afforded at race amount of the borylated product with poor regioselectivity (Table 1, entries 1a nd 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations